Androgen receptor in triple negative breast cancer: A potential target for the targetless subtype. (July 2018) - Gerratana, L.; Basile, D.; Buono, G.; De Placido, S.; Giuliano, M.; Minichillo, S.; Coinu, A.; Martorana, F.; De Santo, I.; Del Mastro, L.; De Laurentiis, M.; Puglisi, F.; et al.
Highlights: The AR positive subtype has better prognosis and less chemotherapy responsiveness. AR is involved in cell cycle regulation and Epithelial-to-Mesenchymal Transition. Clinical data demonstrate the efficacy of antiandrogen therapies for AR positive TNBC. Abstract: Triple negative breast cancer (TNBC) represents the 15–20% of all breast cancers (BC) and is characterized by a very aggressive behavior. Recent data suggest that TNBC is not a single disease, but it is rather an umbrella for different ontology-profiles such as basal like 1 and 2, mesenchymal, and the luminal androgen receptor (LAR). The LAR subtype is characterized by the expression of the Androgen Receptor (AR) and its downstream effects. Notwithstanding the role of the AR in several signaling pathways, its impact on a biological and clinical standpoint is still controversial. The LAR subtype has been associated with better prognosis, less chemotherapy responsiveness and lower pathologic complete response after neoadjuvant treatment. Clinical evidence suggests a role for anti-androgen therapies such as bicalutamide, enzalutamide and abiraterone, offering an interesting chemo-free alternative for chemo-unresponsive patients, and therefore potentially shifting current treatment strategies.